Sub-Analysis of CYP-GUIDES Data: Assessing the Prevalence and Impact of Drug-Gene Interactions in an Ethnically Diverse Cohort of Depressed Individuals - Crutchley, Rustin D.; Keuler, Nicole (Frontiers in Pharmacology, 2022)
Introduction Minority groups are underrepresented in pharmacogenomics (PGx) research. Recent sub-analysis of CYP-GUIDES showed reduced length of stay (LOS) in depressed patients with CYP2D6 sub-functional status. Our primary objective was to determine whether PGx guided (G) versus standard treatment (S) influenced LOS among different ethnicities. Secondary objectives included prevalence of drug-gene interactions (DGIs) and readmission rates (RAR). Methods Retrospective sub-analysis of CYP-GUIDES data was performed with CYP2D6 functional status reclassified using standardized CYP2D6 genotype to phenotype recommendations from Clinical Pharmacogenomics Implementation Consortium (CPIC) and Dutch Pharmacogenetics Working Group (DPWG). The Mann-Whitney test was used to determine differences in LOS between groups G and S and Kruskal Wallis test to compare LOS among different ethnicities. Logistic regression was used to determine covariates associated with RAR. Results This study included 1,459 patients with 67.3% in G group (n=982). Majority of patients were White (57.5%), followed by Latinos (25.6%) and Blacks (12.3%). Although there were no differences in LOS between G and S groups, Latinos and Blacks had significant shorter LOS than Whites. LOS was significantly reduced by 5.6 days in poor metabolizers in group G compared to S (p=0.002). Proportion of supra functional and ultra-rapid metabolizer (URMs) were 6% and 20.3% using CYP-GUIDES and CPIC/DPWG definitions, respectively. Prevalence of DGIs was 40% with fewer DGIs in Blacks. Ethnicity was significantly associated with RAR (aOR 1.30; p= 0.003). Conclusion Greater number of patients were classified as CYP2D6 URMs using CPIC/DPWG definitions. This finding may have clinical implications for using psychotropics metabolized by CYP2D6.